Developing a practical framework for the recruitment and retention of radiographers in the public sector of KwaZulu-Natal Province, South Africa - Cibane, Nonkululeku; Hoque, Muhammad (Orapuh Journal, 2024)
Introduction There is a notable lack of strategic recruitment and retention initiatives for radiographers in KwaZulu-Natal Province. This is evident in the disproportionate ratio of radiographers to the population they serve and the imbalance between those employed in the public and private healthcare sectors. Purpose This study aimed to develop a comprehensive framework to improve the recruitment and retention of public sector radiographers in KwaZulu-Natal by examining relevant policies and regulations, as well as gathering insights from both service-level and managerial radiographers. Methods A sequential exploratory mixed-methods approach was employed, incorporating a document review, a cross-sectional survey of a stratified random sample of 220 radiographers, and in-depth interviews with a purposive sample of ten radiography managers from various public hospitals in KwaZulu-Natal. Thematic analysis was used for the document review and interviews with managers, while logistic regression was applied to identify significant predictors of retention in the quantitative data. Results The document review revealed that, although policies and procedures for recruitment and retention exist, the radiography profession is poorly regarded within the broader healthcare field. Radiographers are underrepresented in decision-making bodies and lack an advisory board. The intention to leave the profession was significantly influenced by factors such as incentives (p=0.030) and burnout (p=0.007). Participants highlighted several barriers to effective recruitment and retention, including inadequate policy implementation, insufficient support and recognition, and limited opportunities for career advancement. Conclusion The proposed framework emphasizes the importance of advocating for the radiography profession in decision-making forums, ensuring the effective implementation and monitoring of recruitment policies, improving the work environment, and enhancing career development pathways for radiographers.